Effect of Probiotic Administration of Bacillus subtilis and Bacillus coagulans Isolate on Growth Performance in Broiler Chicken - Faiqoh, Berliana Elok; Lamid, Mirni; Damayanti, Ratna; Chusniati, Sri; Al Arif, Mohammad Anam; Warsito, Sunaryo Hadi; Lestari, Tita Damayanti; Raharjo, Hartanto Mulyo; Rehman, Saifur; Hussain, Muhammad Asif (Universitas Airlangga, 2023)
This study aimed to determine the effect of probiotic administration of Bacillus subtilis and Bacillus coagulans isolate in improving feed intake, and body weight, and feed conversion rate (FCR) in broiler chicken. A total of 24 broiler chickens divided into four treatments i.e. (P0) was a group without probiotics, (P1), (P2), and (P3) were experimental treatment groups consist of probiotic 2 mL/day, 4 mL/day, and 6 mL/day per orally. In results, feed intake, body weight, and FCR values in all treatment groups (P1, P2, P3) were significantly different (p < 0.05) from (P0) group. Meanwhile, there was no significant difference (p > 0.05) between P1 and P3 group. It can be concluded that the effect of B. subtilis and B. coagulans as probiotics with a dose of 4 mL/day had a noticeable impact on feed intake, body weight, and decreased FCR.